(untitled) (Ozone Therapy Global Journal, 2013)
Coronary arte ry disease (CAD) is the mo st c om mo n c aus e of death in western societie s. Epid emiological studies have found that p l asma concentration of high density lipoproteins (HDL) correlates inversely with the incidence of CAD. The quality and functionality of HDL, more than quantity, appears to be an important predictor of antiatherogenic properties of these particles. Epidemiological evidence demonstrates that low HDL-paraoxonase activity is associated with increased risk of cardiovascular disease. Evidence that antioxidant enzymes, and other subcellular activities could be modulated by low doses of ozone is now proven and support itsclinical a pplication. The aim of the prese nt s tudy was to evaluate t he effect of ozone therapy on paraoxonase 1 lactonase activity and lipid damage in CAD patients. We included 52 pa tients in the clinical study. The first g roup (n=26) recei ved 20 sessi ons of ozone (40μg/mL; 200 mL) by rectal insufflation, meanwhile the second one was treated with oxygen only (n=2 6, co ntro l group). A t the end of the study we determ i ned spectrophotometri cally the paraoxonase-lactonase activity, and the LDL and serum susceptibility to lipid peroxidation. The results showed that ozone therapy was able to red uce the malondialdehyde levels in trea ted p atie nts at the same tim e tha t paraoxonase 1 lactonase a ctivity w as sign i ficantly (p<0. 05) increased. Our results suggestthat ozone may be used in combination with the conventional drugs for CAD therapy. Nevertheless, future clinical trials will be necessary to establish how long HDL antioxidant status is maintained after therapy and how often it will be nec essary to repeat the ozone treatment.